Infection-specific PET imaging with 18F-fluorodeoxysorbitol and 2-[18F]F-ρ-aminobenzoic acid: An extended diagnostic tool for bacterial and fungal diseases - Rua, Marta; Simón, Jon Ander; Collantes, María; Ecay, Margarita; Leiva, José; Carmona-Torre, Francisco; Ramos, Rocío; Pareja, Félix; Pulagam, Krishna R.; Llop, Jordi; Del Pozo, José Luis; Peñuelas, Iván (Frontiers in Microbiology, 2023)
Suspected infectious diseases located in difficult-to-access sites can be challenging due to the need for invasive procedures to isolate the etiological agent. Positron emission tomography (PET) is a non-invasive imaging technology that can help locate the infection site. The most widely used radiotracer for PET imaging (2-deoxy-2[18F]fluoro-ᴅ-glucose: [18F]FDG) shows uptake in both infected and sterile inflammation. Therefore, there is a need to develop new radiotracers able to specifically detect microorganisms. Here we tested two specific radiotracers: 2-deoxy-2-[18F]-fluoro-ᴅ-sorbitol ([18F]FDS) and 2-[18F]F-ρ-aminobenzoic acid ([18F]FPABA), and also developed a simplified alternative of the latter for automated synthesis. Clinical and reference isolates of bacterial and yeast species (19 different strains in all) were tested in vitro and in an experimental mouse model of myositis infection. Non-lactose fermenters (Pseudomonas aeruginosa and Stenotrophomonas maltophilia) were unable to take up [18F]FDG in vitro. [18F]FDS PET was able to visualize Enterobacterales myositis infection (i.e., Escherichia coli) and to differentiate between yeasts with differential assimilation of sorbitol (i.e., Candida albicans vs. Candida glabrata). All bacteria and yeasts tested were detected in vitro by [18F]FPABA. Furthermore, [18F]FPABA was able to distinguish between inflammation and infection in the myositis mouse model (E. coli and S. aureus) and could be used as a probe for a wide variety of bacterial and fungal species.